Sialendoscopy for the management of juvenile recurrent parotitis: A systematic review and meta‐analysis. (13th November 2014) - Ramakrishna, Jayant; Strychowsky, Julie; Gupta, Michael; Sommer, Doron D.
<x xml:space="preserve">Abstract</x> Objective To determine the effectiveness and safety of sialendoscopy for the treatment of juvenile recurrent parotitis (JRP). The study was conducted and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Data Sources A comprehensive search strategy in MEDLINE, EMBASE, the Cochrane library, and Google Scholar was completed and limited to studies published in English. Relevant reference lists were reviewed. Study Selection Two independent reviewers selected prospective or retrospective studies of pediatric patients treated with interventional sialendoscopy for the management of JRP. Outcome measures included rates of successful treatment (no further episodes of parotid swelling or need for further sialendoscopy) and complications, Data Extraction Two reviewers appraised the level of evidence using the Oxford Clinical Evidence‐based Medicine (OCEBM) guidelines, extracted data, and resolved discrepancies by consensus. Weighted pooled proportion, 95% confidence interval (CI), and test results for heterogeneity and publication bias are reported. Results Seven studies were included. Levels of evidence varied from OCEBM level 3 to 4. The weighted pooled proportion of success rates for no further episodes by patient (n = 120) was 73% (95% CI: 64%‐82%) and by gland (n = 165) 81% (95% CI: 75%‐87%). The weighted pooled proportion of success rates for no further sialendoscopy by patient was 87% (95% CI: 81%‐93%). Heterogeneity was low, and publication bias was not detected. There were no major complications reported. Surgical techniques and endoscopic findings are summarized. Conclusions The results from this analysis suggest that sialendoscopy is effective and safe for the treatment of JRP and may be offered to appropriate patients. Level of Evidence NA Laryngoscope, 125:1472–1479, 2015